'Counting black and white beans' : critical race theory in accounting - Lewis, Anton (Emerald Publishing Limited, 2020)
Across the US and the UK, few senior accountants exist in proportion to their white peers, and only a handful ever reach the level of partner in large accounting firms. This problem has been left largely unexamined on both sides of the Atlantic and is overwhelmingly disregarded due to an inherent assumption of racial neutrality within the field of accountancy. This book unpacks the lived working experience of black accountants in the US and UK to highlight the existence of institutionalized racism. Using the perspective of Critical Race Theory (CRT), Anton Lewis demonstrates how the black accountant is in fact an outsider, with limited options for professional progress. He offers a qualitative, narrative-focused approach, exploring detailed testimonies of Black British and African American accountants within a CRT theoretical framework, to highlight how the field of accounting has participated in a historic system of racial and professional inequities. This book invites the reader to critically examine how black people enter and progress in the field and comprehend the processes by which black accountants understand the impact race has on their professional identities. Looking at the way forward, the author also serves up practical guidelines for black accountants on how to network, and how best to strategize for success across their careers from entry level positions, to senior professionals seeking partnership.
Chapter 1: The Black Bean Counter -- Chapter 2: Accounting for Critical Race Theory -- Chapter 3: A History of Accounting and Race -- Chapter 4: The Black Ledger -- Chapter 5: The White Ledger -- Chapter 6: The Tales We Tell -- Chapter 7: Race and Place -- Chapter 8: Epilogue.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: African American accountants; Accounting -- United States; Accounting -- Great Britain; Discrimination in employment -- United States; Discrimination in employment -- Great Britain; Business & Economics -- Accounting -- General; Accounting